Rahmah El Yunusiyah: Tokoh Pembaharuan Pendidikan di Kalangan Perempuan Minangkabau, 1923-1969 - Muhammad Ihsan Syahaf Nasution; Hafnita Sari Dewi Lubis; Yushar Tanjung (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This article aims to analyze the dynamics of islamic education renewal that occurs among women in the Minangkabau region spearheaded by Rahmah El Yunusiyah. The main issue raised in this article is related to the efforts to renew education among women carried out by Rahmah El Yunusiyah so that it has its own characteristics in the development of education, especially in Minangkabau. The method used in this study is a historical method as a tool to see the development of the renewal efforts carried out by Rahmah El Yunusiyah in the field of education. The results of the study found that Rahmah El Yunusiyah was able to renew education among women in the Minangkabau through Diniyyah School Poetri. This can be seen from the development of the school he founded, starting from the side of the building to the alumni produced. This then became a reference for several educational institutions in Indonesia to follow the education system implemented in the school. In addition, the renewal in the field of education among women carried out by Rahmah El Yunusiyah was able to raise the position of women in Minangkabau society.